A comprehensive introduction to outrigger and belt-truss system in skyscrapers. (October 2020) - Alhaddad, Wael; Halabi, Yahia; Xu, Hu; Lei, HongGang
Abstract: Outrigger and belt-truss system is one of the most common lateral load resisting systems in tall and super tall buildings. The prevalence of this system is a result of its efficiency, which has been clarified and proved through a massive number of researches that discussed and investigated various aspects related to the outrigger and belt-truss system. Therefore, combining and summarizing the main points and methodologies in previous studies through a comprehensive review is essential in order to provide guidance for designers and researchers, especially those who are newly dealing with this area of research. Due to the vast research area of this system, the paper only will illustrate the components, configurations, types of outrigger system from a different point of views, factors that affect the performance, the structural behavior of the system under various loading types, the pros and cons of outrigger system, in addition to a summary for the main design issues which will be discussed in later reviews. Consequently, this article can be considered as a focal point for the researchers and designers in order to establish a deep understanding of this system, besides, to avoid as much as possible of the system's drawbacks, thereby leading to more efficient employment of outrigger system and give the ability to integrate this system into design provisions and guidelines.